2021
DOI: 10.3311/ppci.16944
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Composite Shear Walls Subjected to In-plane Cyclic Loading - A Numerical Parametric Study

Abstract: An RC shear wall (wall1), a composite shear wall composed of a single external steel plate connected to a concrete panel (wall2), a composite shear wall constructed from two external steel plates connected to an internal concrete panel (wall3) and finally a composite shear wall fabricated with a single internal steel plate embedded within a concrete panel (wall4) are considered in this study and their behavior are assessed and compared under the effect of an in-plane cyclic load. Variation of the three functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Nevertheless, the energy dissipation capacity is much higher for this type of structural walls in comparison with other structural systems. The axial compression ratios, the strength of concrete in compression or the steel ratios embedded in the edges of the walls, are other parameters that present a significant impact over the hysteretic performance of composite steel-concrete shear walls, as Hu et al (Hu, 2021) and Labibzadeh et al (Labibzadeh, 2021) recorded in their research. In many studies found in the literature, the influence of these parameters on the seismic behaviour of the structural walls is investigated by performing numerical analyses besides the experimental tests, using finite element method and software's.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, the energy dissipation capacity is much higher for this type of structural walls in comparison with other structural systems. The axial compression ratios, the strength of concrete in compression or the steel ratios embedded in the edges of the walls, are other parameters that present a significant impact over the hysteretic performance of composite steel-concrete shear walls, as Hu et al (Hu, 2021) and Labibzadeh et al (Labibzadeh, 2021) recorded in their research. In many studies found in the literature, the influence of these parameters on the seismic behaviour of the structural walls is investigated by performing numerical analyses besides the experimental tests, using finite element method and software's.…”
Section: Introductionmentioning
confidence: 97%